Personalized treatment of extensive stage small cell lung cancer: A case report and literature review - Huaiyu Wang; Xuning Wang; Suxin Jiang; Jingna Zhu; Jie Liu; Chuanhong Zhou; Yanjun Zhu; Yong Han (Frontiers in Oncology, 2022)
A 50-year-old female patient presented with post-exercise dyspnea in September 2016, and was subsequently diagnosed with SCLC with multiple brain and spinal metastases. The first-line treatment was etoposide combined with cisplatin and synchronously performed radiotherapy for the brain and spinal cord metastases. She was treated with anlotinib after disease progression in December 2018 and continued to have clinical benefit for nearly 25 months. Unexpectedly, the patient can still benefit from further combination treatment with durvalumab after another disease progression in February 2021. Thus, it may be a potential option to use anlotinib along with immunotherapy after the anlotinib resistance in SCLC, but more clinical data are still needed to confirm it. Moreover, ctDNA dynamic monitoring was performed and reflected the outcome of the process of treatment.